Routing scheme for macro mobility handover in hierarchical mobile IPv6 network - Vivaldi, Indra; Mohd Ali, Borhanuddin; Habaebi, Mohamed Hadi; Prakash, V.; Sali, A. (IEEE, 2003)
Significant problems in basic mobile IPv6 occur due to its inability to support micro-mobility because of long delay and high packet loss during handover. Hierarchical mobile IPv6 (HMIPv6) as an extension of basic Mobile IPv6 solves the problem by separating the handover management to macromobility and micro-mobility. HMIPv6 introduced a new protocol element called Mobility Anchor Point (MAP) to manage the mobility. HMIPv6 can reduce the delay and the amount of signaling during handover. However the protocol still cannot meet the requirement for traffic that is delay sensitive such as voice especially in macro mobility management. Duplicate address detection and the transmission time for the handover operation could cause high handover delay.